2020
DOI: 10.26434/chemrxiv.11592018.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Quest for the Ideal Base: Rational Design of a Nickel Precatalyst Enables Mild, Homogeneous C–N Cross-Coupling

Abstract: Palladium-catalyzed amination reactions using soluble organic bases have provided a solution to the many issues associated with heterogeneous reaction conditions. Still, homogeneous C–N cross-coupling approaches cannot yet employ bases as weak and economical as trialkylamines. Furthermore, organic base-mediated methods have not been developed for Ni(0/II) catalysis, despite some advantages of such systems over analogous Pd-based catalysts. We designed a new air-stable and easily prepared Ni(II) precatalyst bea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…For example, Liu et al found that [Ni(COD)2]/dppf was not a competent catalyst for the cross-coupling of phenyl triflate and aniline, but that a modified ligand (1,1'-bis(di(3,5-trifluoromethylphenyl)phosphino)ferrocene) enabled the reaction to achieve almost quantitative conversion. 6 There are many examples of situations where the mechanisms of nickel-catalysed reactions can also be very sensitive to ligand structure. If the nickel-catalysed Suzuki-Miyaura coupling of benzylic esters is carried out using tricyclohexylphosphine as the ligand the stereochemistry at the benzylic position is retained; however, the use of SIMes produces the stereoinverted product via a different mechanistic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Liu et al found that [Ni(COD)2]/dppf was not a competent catalyst for the cross-coupling of phenyl triflate and aniline, but that a modified ligand (1,1'-bis(di(3,5-trifluoromethylphenyl)phosphino)ferrocene) enabled the reaction to achieve almost quantitative conversion. 6 There are many examples of situations where the mechanisms of nickel-catalysed reactions can also be very sensitive to ligand structure. If the nickel-catalysed Suzuki-Miyaura coupling of benzylic esters is carried out using tricyclohexylphosphine as the ligand the stereochemistry at the benzylic position is retained; however, the use of SIMes produces the stereoinverted product via a different mechanistic pathway.…”
Section: Introductionmentioning
confidence: 99%